Implementation of the Oriko for Adikoeva (8i) Simulation Method to Improve 21st Century Skills in Science Learning in Elementary Schools - Ricky Avandra; Darmansyah; Yeni Karneli; Muhammadi (Universitas Pendidikan Ganesha, 2025)
The learning process in the modern era should focus on developing 21st-century skills, including critical thinking, creativity, collaboration, and communication. However, these skills are still relatively low, causing students’ potential and abilities to remain underdeveloped. This study aims to analyze the improvement of 21st-century skills through the implementation of the Oriko for Adikoeva (8i) simulation method in science learning. The method consists of eight stages orientation, collaboration, formulation, action, discussion, communication, evaluation, and appreciation which integratively foster students’ critical thinking, collaboration, creativity, and communication skills. This research employed a descriptive qualitative approach with a classroom action research design conducted in two cycles. Data were collected using observation sheets and test instruments, and analyzed descriptively and comparatively to identify improvements in both student skills and teacher performance. The results indicate that the application of the Oriko For Adikoeva (8i) simulation method significantly enhanced students’ 21st-century skills. Improvement was also observed in teachers’ ability to design and implement learning activities. These findings imply that integrating simulation methods based on collaborative and reflective activities can be an effective strategy to strengthen elementary students’ competencies for the 21st century.